2010
DOI: 10.3109/00016357.2010.514720
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Treatment on Bonding Between Zirconia Ceramic Surface and Resin Cement

Abstract: All surface treatment methods improved the bond strength between resin cement and the zirconium oxide ceramic surface. CO₂ laser etching may represent an effective method for conditioning zirconia surfaces, enhancing micromechanical retention and improving the bond strength of resin cement on zirconia ceramic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 25 publications
5
83
1
10
Order By: Relevance
“…It was thus recommended as an alternative surface treatment technique for bonding resin cement to zirconia ceramic surfaces 44,45) . However, Paranhos et al 35) reported that significant microcracks were found on specimens treated with the CO 2 laser (5W) and that low SBS values were obtained with the same resin cements used in previous study.…”
Section: Discussionmentioning
confidence: 99%
“…It was thus recommended as an alternative surface treatment technique for bonding resin cement to zirconia ceramic surfaces 44,45) . However, Paranhos et al 35) reported that significant microcracks were found on specimens treated with the CO 2 laser (5W) and that low SBS values were obtained with the same resin cements used in previous study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of hydrofluoric acid etching for zirconia is limited owing to the small amount of silica-based phase in the material. Hydrofluoric acid etching does not produce morphological changes or sufficiently roughen the surfaces of high strength ceramics such as aluminum-oxide ceramics and zirconia ceramics 34,35) . In the current study, hydrofluoric acid did not improve bond strength between a gingiva-colored indirect composite and zirconia ceramics, which is consistent with previous findings 35) .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrofluoric acid etching does not produce morphological changes or sufficiently roughen the surfaces of high strength ceramics such as aluminum-oxide ceramics and zirconia ceramics 34,35) . In the current study, hydrofluoric acid did not improve bond strength between a gingiva-colored indirect composite and zirconia ceramics, which is consistent with previous findings 35) . In the current study, the surface roughness values of NT, HF and HT groups were found to be significantly higher than those of SiC 600, 1500 and AB 0.1 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ural et al [7] have studied the effect of laser treatment on the bonding between zirconia ceramic surface and resin cement which has a clear effect on the microstructure of bonding region.…”
Section: Introductionmentioning
confidence: 99%